Inhibiting of GRASP65 Phosphorylation by DL-3-N-Butylphthalide Protects against Cerebral Ischemia-Reperfusion Injury via ERK Signaling - Bei-lei Zhu; Chen-long Xie; Ning-ning Hu; Xin-bo Zhu; Chun-feng Liu (Behavioural Neurology)
Background and Purpose. The aim of this study was to explore the role of DL-3-n-butylphthalide (NBP) in cerebral ischemia-reperfusion injury (CIRI) mice model. The involvement of extracellular signal-regulated kinase (ERK) signaling pathway was also investigated. Methods. All mice were divided into five groups: sham-operated group, CIRI group, NBP pretreatment group, NBP treatment group, and NBP pretreatment + treatment group. The CIRI mice model was established by the use of the Pulsinelli four-vessel occlusion method. Pretreatment mice received NBP (90 mg/kg/d) three times a day within four days before reperfusion by gavage. Treatment mice received NBP (90 mg/kg/d) three times a day within five days after reperfusion by gavage. We detected the infarction area, the neurological severity, and the superoxide dismutase and malondialdehyde levels. Furthermore, we observed the expressions of GRASP65, phosphorylation of GRASP65 (pGRASP65), ERK, and phosphorylation of ERK (pERK) by the use of Western blotting. Results. The result showed that the ERK pathway was activated in response to CIRI. NBP decreases the expressions of pERK and pGRASP65 following CIRI. Additionally, NBP could decrease MDA and increase SOD level in brain tissues. Decreased infarct volume was also observed in the NBP group. Thereby, NBP inhibited the activation of the ERK pathway induced by CIRI and reduced the GRASP65 phosphorylation. Conclusions. The current finding suggested that NBP protected the cerebrum from CIRI mediated by inhibiting the ERK signaling pathway and subsequently reducing GRASP65 phosphorylation.